2022
DOI: 10.5114/polp.2022.123913
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations of the Polish Paediatric Society, the Polish Society of Vaccinology, and the Polish Society of Family Medicine on meningococcal vaccinations in children and adults in Poland

Abstract: Invasive meningococcal disease is a dangerous bacterial infection that often leads to death or permanent disability. Immunization is the best strategy to protect individuals against invasive infections caused by Neisseria meningitidis. The effectiveness of vaccines has been demonstrated in many countries where they have been introduced into national vaccination programs. Meningococcal vaccinations in Poland are recommended in the framework of the National Immunization Program. However, they are not reimbursed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…For many years in Poland, the majority of cases of invasive meningococcal disease have been caused by type B bacteria [ 43 ]. Meningococcal vaccination is recommended for adults and children, with an emphasis on starting vaccination as early as possible, as meningococci are more dangerous the younger a child is [ 44 ]. The present study showed that the use of paid pneumococcal vaccination was associated with more frequent vaccination against meningococcal C infection and, more broadly, A, C, W135, and Y infection, as these types were part of the polyvalent vaccine used fairly frequently.…”
Section: Discussionmentioning
confidence: 99%
“…For many years in Poland, the majority of cases of invasive meningococcal disease have been caused by type B bacteria [ 43 ]. Meningococcal vaccination is recommended for adults and children, with an emphasis on starting vaccination as early as possible, as meningococci are more dangerous the younger a child is [ 44 ]. The present study showed that the use of paid pneumococcal vaccination was associated with more frequent vaccination against meningococcal C infection and, more broadly, A, C, W135, and Y infection, as these types were part of the polyvalent vaccine used fairly frequently.…”
Section: Discussionmentioning
confidence: 99%